Trajetórias profissionais: uma pesquisadora aprendendo com narrativas de professores que ensinam Matemática no 5º ano - Donêncio, Márcia Maria (2021)
In this investigation, I discuss the professional trajectory of pedagogues who work in the fifth years of a municipal school system. It was developed during the Professional Master's in Teaching in Basic Education of the Stricto Sensu Graduate Program of the Center for Teaching and Research Applied to Education - CEPAE of the Federal University of Goiás - UFG, between the years 2018 to 2021 Our trajectory professional has relevant brands, singularities and experiences. These experiences need to be shared and thus inspire other teachers on their own paths. Thus, it becomes relevant to present narratives, oral and written, together with these teachers; know a little about their life history; discuss with them how they seek to (re)signify (or not) their practice in the classroom, seeking evidence of their knowledge, their experiences. For this research, the methodology adopted was Narrative Research (CLANDININ; CONNELLY, 2015), since the teachers' narratives are loaded with their trajectories and constitute rich material in the training of other teachers. We started with a semi-structured interview to collect data and produce pedagogical narratives by these professionals. We have the collaboration of four teachers who work in the fifth year of Elementary School I (colleagues by profession), as well as our own professional trajectory. We built our training memorial and confronted it with the trajectories lived by our colleagues and presented in their interviews and pedagogical narratives. We realize that the stories of the teachers are related. Teachers look alike. And the stories of some contribute to the development and construction of the stories of others. Thus, shared experiences are of great importance in this process. As the narratives presented by the collaborators in this research were very rich, with their analysis I produced the Educational Product that accompanies this work, a book entitled CONTE, PROFESSOR PEDAGOGO! The professional trajectory of teachers who teach Mathematics in the fifth year. It presents the analyzes and reflections arising from this investigation and the results that I reached throughout the research.